Preparation and photochromic properties of phosphomolybdic acid/rare earth strontium aluminate luminous fiber. (12th August 2020) - Li, Jing; Tang, Sisi; Ge, Mingqiao; Zhu, Yanan; Yu, Yuan
Abstract: In this study, we intend to obtain a novel luminous fiber with colour-tuned luminescence via the photoelectron transfer of a phosphomolybdic acid pigment (PAP). The luminous fiber include the SrAl2 O4 : Eu 2+, Dy 3+ materials as the luminescence sources, a solid solution of PAP and polyvinyl alcohol as the photoinitiator, amino silicone resin (ASR) as the surface-modified film-forming material and polypropylene (PP) as the matrix, which are prepared by the melt spinning method. The surface morphology was characterized using scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible (UV–vis) spectroscopy, photoluminescence emission spectroscopy, and CIE-1931 chromaticity coordinates. Thus, promising results were obtained, which denoted that the luminescence colour of the luminous fibers could transform from yellow–green to blue by adjusting the PAP concentration. The PL emission spectra of these luminous fibers consisted of two emission peak regions in the range of 430–530 nm. The intensity of the two emission peaks in the fiber reaches the maximum when the concentration of the PAP was 50%. Further, the fibers gradually turned blue with luminescence decay when the fiber was placed in a dark place. The existence of photosensitive discoloration was found to be directly related to the amino groups embedded in the silicone resin coated with the luminous surface material, which reacted with PAP to develop phosphorous molybdenum blue via the photo-reduction process. These findings provide valuable insights toward developing next-generation luminescent materials and multicolor luminous fibers.